Pola Asuh Makan, Pengetahuan Ibu dan Status Ekonomi Orang Tua pada Balita dengan Status Gizi Bermasalah di Pusat dan Pinggir Kota - Syafyanti, Syafyanti; Hasniyati, Rina; Rukmana, Silfira Asri; Yuniarti, Elsyie; Andrafikar, Andrafikar (Jurnal Sehat Mandiri, 2023)
The toddler years are the most important period, where children need adequate nutrition to support their physical growth. This study aims to determine the description of parenting patterns, mothers’ knowledge level, and parents' economic status for toddlers with problem nutritional status in the city center and outskirts of the city in the work area of ​​the Gambok Health Center, Sijunjung Regency in 2022. This research is a descriptive study with a cross-sectional study design. The population in this study was toddlers with problematic nutritional status (undernutrition and overnutrition) totaling 60 people. Collecting data using a questionnaire and direct measurement of the height and weight of children under five. The research results were analyzed univariately and displayed in the form of a frequency distribution table. The results of this study indicate that more than half of the bad parenting patterns (75%) in toddlers are found in the outskirts of the city, while in the city center, the parenting patterns are good (100%). More than half of the mothers (82.5%) have a good level of knowledge living in the city center, while more than half of the mothers (60%) have a low level of knowledge living in the Outskirts of the City. The economic status of parents in the City Center (95%) and Outskirts of the City (50%) already have sufficient economic status. Based on this, it can be concluded that parenting patterns, mothers’ level of knowledge, and parents' economic status are some of the factors that cause toddlers to have problematic nutritional status. This research can be developed by adding other factors that can affect the nutritional status of toddlers.